TANTANGAN PARENTING DALAM MEWUJUDKAN MODERASI ISLAM ANAK - Astuti, An Ras Try; Herman, Hardiyani; Hadawiah, Rabiatul; Ardiyanti, Nurul (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2018)
The birth of X, Y, Z and Alpha generations cannot be denied, given the rapid development of technology. The formation of the character of Alpha Generation or Gen-A which was born in 2010 is a concern and a challenge for parents in shaping the personality of a civilized and humanitarian child. This article is motivated by a critical review of the conditions of intolerance among religious people. Where the soul of intolerance that arises in a person is due to the absence of a sense of humanity and civilized human elements in themselves. One of the main causes is the influence of misuse of technology which has led to the birth of the Alpha Generation that is enslaved by technology. A person's social life deteriorates so that he does not respect differences. The use of technology well can avoid the anti-tolerant nature and be able to form prospective generations who are civilized and humane in accordance with Islamic values. The provision of technological education for children of old age can not be separated from the role of parents as the first madrasa for children. The habit of children will be difficult to change when from the beginning parents do not do education in the family through parenting education. Parenting education is one of the efforts made by parents in educating, nurturing and teaching children.